2016
DOI: 10.1007/s00404-016-4176-9
|View full text |Cite
|
Sign up to set email alerts
|

WTIP interacts with BRCA2 and is essential for BRCA2 centrosome localization in cervical cancer cell

Abstract: This study indicates that WTIP interacts with BRCA2 and might be responsible for BRCA2 centrosome localization in cervical cancer cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Modulation of WTIP can lead to the kidney-cell scarring (e.g., focal segmental glomerulosclerosis) that is characteristic in diabetes mellitus 40,41 . Thus, alterations to WTIP may be associated with obesity associated comorbidities, including diabetes 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Modulation of WTIP can lead to the kidney-cell scarring (e.g., focal segmental glomerulosclerosis) that is characteristic in diabetes mellitus 40,41 . Thus, alterations to WTIP may be associated with obesity associated comorbidities, including diabetes 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Wt1-interacting protein (WTIP), an Ajuba family LIM domain scaffold protein expressed in podocytes, coordinates cell adhesion changes and transcriptional responses to regulate podocyte phenotypic plasticity 28. Downregulation of WTIP abolished BRCA2 centrosome localization and abnormal cell division in HeLa cells 29. It has been reported that WTIP can work as a crucial point of crosstalk between EGFR and Hippo signaling and suppress the Hippo pathway 30.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that WTIP is a candidate tumor suppressor. In cervical cancer cells, downregulation of WTIP abolished BRCA2mediated centrosome localization and resulted in abnormal cell division, suggesting that WTIP might be involved in the development of cervical cancer [19]. A recent study reported that WTIP is downregulated in NSCLC, and low levels of WTIP are associated with poor prognosis in NSCLC patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of mammalian P-body associated protein, WTIP is involved in miRNA-mediated gene silencing in human osteosarcoma cells [18]. In cervical cancer cells, downregulation of WTIP abolished BRCA2-mediated centrosome localization and resulted in abnormal cell division, suggesting that WTIP might be involved in the development of cervical cancer [19]. Recently, it was demonstrated that WTIP protein expression is significantly reduced in non-small-cell lung cancer (NSCLC) cells, and WTIP downregulation is associated with poor prognosis in NSCLC patients [20].…”
Section: Introductionmentioning
confidence: 99%